Formulation and evaluation of hard capsules containing Passiflorae foetidae soft extract - Nguyen, Thị Huyền; Vu, Lê Hà; Huynh, Lời (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
Passiflora foetida L. (Passifloraceae) is a vine with soft stems and covered with hairs. The herb grows in wild with alternate leaf, large flower, berry-like fruit. Passiflora foetida has a sedative effect and is used for treatment of insomnia and neurasthenia. Passiflora foetida has two main chemical components including flavonoids, and alkaloids. Vitexin, the flavonoids, is found in Passiflora foetida which was used as a marker for qualitative and quantitative purposes. The aim of this study was to formulate the hard capsule dosage form containing Passiflora foetida soft extract. Ethanol 96% was investigated as the solvent for extraction. The ratio of solvent and medicinal ingredients was 1:7. The quantitative UV-Vis method showed a good linear correlation between vitexin concentration and absorbance at 401 nm. The total flavonoid content was expressed as vitexin in the hard capsule of about 1.16%. The hard capsules containing Passiflora foetida soft extract were successfully prepared and tested to meet the quality requirements in Vietnamese Pharmacopoeia V.